Bank liquidity, interbank markets, and monetary policy - Xavier Freixas; Antoine Martin; David Skeie (Federal Reserve Bank of New York, 2009)
A major lesson of the recent financial crisis is that the interbank lending market is crucial for banks that face uncertainty regarding their liquidity needs. This paper examines the efficiency of the interbank lending market in allocating funds and the optimal policy of a central bank in response to liquidity shocks. We show that, when confronted with a distributional liquidity-shock crisis that causes a large disparity in the liquidity held by different banks, a central bank should lower the interbank rate. This view implies that the traditional separation between prudential regulation and monetary policy should be rethought. In addition, we show that, during an aggregate liquidity crisis, central banks should manage the aggregate volume of liquidity. Therefore, two different instruments-interest rates and liquidity injection-are required to cope with the two different types of liquidity shocks. Finally, we show that failure to cut interest rates during a crisis erodes financial stability by increasing the probability of bank runs.
Keywords: G21; E43; E52; E58; 330; Bank liquidity; interbank markets; central bank policy; financial fragility; bank runs; Bankenliquidität; Geldmarkt; Schock; Finanzmarktkrise; Zinspolitik; Wirkungsanalyse; Theorie